Estudo da interação do poligodial em modelos de membrana de microorganismos - Gonçalves, Giulia Elisa Guimarães [UNIFESP] (2018)
In this study, polygodial, a natural product belonging to the group of sesquiterpenes, was isolated from hexane extract of leaves of Drimys brasiliensis (Winteraceae). Due to the promising results regarding the antiparasitic potential, we sought to study its interaction with the membrane models through Langmuir monolayers. Tensiometric, spectroscopic and morphological techniques were used to characterize the pure and mixed lipid monolayers. The lipids adopted in this study were choosen because they have different chemical natures, including: DPPC (dipalmitoylphosphatidylcholine), DMPC (dimyristoylphosphatidylcholine), DOPC (dioleoylphosphatidylcholine); DODAB (dioctadecyldimethylammonium bromide); DPPS (dipalmitoylphosphatidylserine); DPPG (dipalmitoylphosphatidylglycerol); DPPE (dipalmitoylphosphatidylalonamine) and cholesterol. The results show that the DPPG monolayer condenses in the presence of the compound, while as other monolayers expand. The presence of the polygodial is able to plot greater instability for a DPPG monolayer - recorded by adsorption kinetics curves and also by its PM-IRRAS spectrum; while, it also brings an apparent stability to the DOPC and cholesterol monolayers. Here, the behavior of some of this monolayers in presence of polygodial isomer(epi-polygodial) was also compared. Spectra in the infrared region allowed us to evaluate the factor “relative intensity”, especially in the bands related to the asymmetric and symmetrical stretches of the methylene group, which are related to a greater or less organization of the monolayer. On the other hand, images of the monolayers by Brewster angle microscopy showed the morphology of the film with the incorporation of the polygodial and epipolygodial. Particularly, there is an increase in the number of domains for DODAB in the presence of polygodial and a different behavior of DPPE monolayer for the two compounds. As conclusion, a presence of a polar head group as well as an unsaturation in the alkyl chain influenced in the intermolecular forces between the polygodial and the lipid monolayer, besides bringing characteristics of greater or lesser fluidity to the monolayer, depending on the lipid. More fluid monolayers, such as DOPC and DODAB, appeared to incorporate the compound better because of more flexible molecular rearrangement. In addition, a change in the configuration of a stereogenic carbon also seems to contribute to changes in the interactions between lipid-compound, being necessary more studies to better clarify the extensions caused by this change.